Hannah's list - Macomber, Debbie (Macomber, Debbie. Blossom Street novel., 2010)
On the anniversary of his beloved wife's death, Michael receives a letter Hannah had written him. She makes one final request-- she's chosen three women, and asks him to consider them as a new wife. He's a man who needs the completeness only love can offer-- and the list leads him to a woman who can help him find it.